Literature Analysis of the Effectiveness of Quizizz in Increasing Student Learning Motivation - Ayuningtyas, Intan; Septiarani, Tara (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
The development of digital technology has had a significant impact on the world of education, particularly in creating more engaging and interactive learning methods. One widely used platform is Quizizz, a quiz-based game application designed to enhance student engagement and motivation. This article aims to analyze literature discussing the effectiveness of Quizizz in improving student learning motivation across various educational levels. The method used is a literature review of previous research findings, both from national and international journals. The findings indicate that the use of Quizizz generally enhances student learning motivation, both from intrinsic and extrinsic aspects. Features such as gamification, immediate feedback, and a competitive yet enjoyable learning atmosphere are key factors in increasing student participation. However, challenges such as limited access to technology and teachers' readiness to integrate this platform into learning are also important considerations. Thus, Quizizz can be an effective learning medium if used appropriately and supported by appropriate pedagogical strategies.